Association of UV Index and Sunscreen Use Among White High School Students in the United States. (11th September 2013) - Everett Jones, Sherry; O'Malley Olsen, Emily; Michael, Shannon L.; Saraiya, Mona
ABSTRACT: BACKGROUND: When used appropriately, sunscreen decreases the amount of ultraviolet (UV) radiation exposure to the skin and is recommended to prevent skin cancer. This study examined the association between annual average UV index and sunscreen use among White, non‐Hispanic youth. METHODS: The 2007 and 2009 national Youth Risk Behavior Survey (YRBS) data were analyzed. The YRBS is a school‐based, cross‐sectional study that uses a 3‐stage cluster sample design to obtain a nationally representative sample of public and private high school students in the United States. Overall response rates were 68% and 72% (N = 14, 041 and 16, 410, respectively). Logistic regression analyzes, controlling for grade, examined whether annual average (mean) UV index where students attend school, a proxy measure of potential sunlight exposure, was associated with sunscreen use. RESULTS: Among White male students, as the mean UV index increased, the adjusted odds of never wearing sunscreen increased (adjusted odds ratio, AOR = 1.15 [95% CI = 1.04, 1.27], p < .01) and the adjusted odds of most of the time or always wearing sunscreen decreased (AOR = 0.85 [0.78, 0.94], p < .01). There was no association between sunscreen use and mean UV index among White female students. CONCLUSION: These findings suggest a need for renewed public health efforts among school, clinical, and public health professionals to promote sunscreen use as part of a comprehensive approach to prevent skin cancer. School and community approaches that passively protect young people from the sun should be considered as a complement to efforts to increase sunscreen use.